Optimalisasi Pengawasan Kinerja Karyawan Business Consultant PT XYZ : Implementasi Sistem RACI Melalui Project Google Spreadsheet - Mochammad Zulvikri; Mukaram Mukaram (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Employee performance monitoring is one of the key factors in human resource management, especially in a dynamic business sector such as futures trading. PT XYZ, a company engaged in futures trading, faces challenges in managing the performance of Business Consultants (BC) which often arise due to lack of clarity in the division of tasks, lack of accountability, and ineffective coordination. This study aims to optimize employee performance supervision at XYZ through the implementation of the RACI (Responsible, Accountable, Consulted, Informed) system integrated with Google Sheets. The research method used is qualitative with a case study approach, where in-depth interviews, observation, and documentation are used to collect data from employees and project managers who are directly involved. The results showed that the RACI system through Google Spreadsheet can clarify employee roles and responsibilities, increase accountability, and facilitate real-time performance monitoring. The modification of the RACI matrix in this spreadsheet also makes it easier for management to improve team collaboration and productivity. Despite technical challenges in its implementation, the system proved effective in optimizing team performance and communication.